Characterization of NMCR‐2, a new non‐mobile colistin resistance enzyme: implications for an MCR‐8 ancestor. (20th August 2020) - Ullah, Saif; Ji, Kai; Li, Jun; Xu, Yongchang; Jiang, Chengjian; Zhang, Huimin; Huang, Man; Feng, Youjun
Summary: MCR‐4 and MCR‐8 are two recently identified members of an ongoing MCR family of colistin resistance. Although that aquatic reservoir for MCR‐4 is proposed, the origin and mechanism of MCR‐8 is poorly understood. Here we report a previously unrecognized non‐mobile colistin resistance enzyme, termed NMCR‐2, originating from the plant pathogen Kosakonia pseudosacchari . NMCR‐2 (551aa) gives 67.3% identity to MCR‐8 (565aa). NMCR‐2 is placed as a progenitor/ancestor for MCR‐8 in phylogeny of MCR members. Genetic study reveals that nmcr‐2 is comparable to mcr‐8 in the ability of producing phenotypic colistin resistance. Biochemical analyses determine that these two enzymes catalyse the transfer of PEA from the donor PE lipid substrate to the recipient lipid A molecule by a putative 'ping‐pong' trade‐off. Further experiment of protein engineering demonstrates that the two motifs (TM region and catalytic domain) of NMCR‐2 are functionally exchangeable with that of MCR‐8, rather than MCR‐1. Physiological impacts of nmcr‐2 and/or mcr‐8 are detected in Escherichia coli, featuring with fitness cost. Evidently, the action and mechanism of NMCR‐2 is analogous to that of MCR‐8. Therefore, our finding underlines that NMCR‐2 might be a possible progenitor of MCR‐8.